Comparison of dosage of intensive upper limb therapy for children with unilateral cerebral palsy: How big should the therapy pill be? - Sakzewski, L.; Provan, K.; Ziviani, J.; Boyd, Roslyn (2015)
therapy (mCIMT) and bimanual therapy on upper limb and individualized outcomes for children with unilateral cerebral palsy. This secondary analysis included two separate randomized trials that compared equal doses (high or low) of mCIMT to bimanual therapy; Study 1 (full dose – 60 h) n = 64 and; Study 2 (half dose – 30 h) n = 18 for children aged five to 16 years with unilateral cerebral palsy. Outcomes for both studies included the Melbourne Assessment of Unilateral Upper Limb Function, Assisting Hand Assessment, Jebsen Taylor Test of Hand Function and Canadian Occupational Performance Measure which were administered at baseline, three and 26 weeks. Mixed linear modelling was used to compare between dose (e.g. “full dose” to “half dose” of either mCIMT or bimanual therapy) on outcomes at three and 26 weeks post-intervention. There were no significant differences between groups at baseline, however, on average the half dose mCIMT group was younger with better hand function compared to the other groups. The full compared to half dose mCIMT group achieved greater gains in bimanual performance at three weeks and dexterity and quality of movement at 26 weeks. There were no between group differences for bimanual therapy doses. Half dose groups receiving either mCIMT or bimanual therapy did not make significant within group gains on any upper limb motor outcome, however gains in occupational performance were clinically meaningful. These results suggest that a half dose (30 h) of either mCIMT or bimanual therapy may not be sufficient to impact upper limb outcomes, but made clinically meaningful gains in occupational performance for school aged children with UCP.